Zero Waste Policy Development: Lessons Learned from Selected Case Studies - Zaman, Atiq (UNEP, 2025)
The transition to a zero-waste and circular economy requires comprehensive policy frameworks, innovative strategies, and multi-stakeholder collaboration. The presentation explores key developments in waste management, zero-waste, and circular economy discourses, highlighting lessons learned from selected case studies. The case of used lead-acid batteries (ULABs) in Bangladesh illustrates the environmental and public health risks posed by informal recycling networks and the need for regulatory harmonisation. Additionally, insights from Western Australia's Circular Horizons (WATCH) initiative demonstrate how lifecycle-focused policies and circular economy integration can drive sustainable material use. The presentation provides key recommendations for policymakers, industry leaders, and researchers to enhance circularity, resource efficiency, and waste minimisation at local, national, and global scales.